Too sensational : on the choice of exchange rate regimes - Corden, W. M. (Warner Max) (Ohlin lectures ;, 2002)
Most of the literature on exchange rate regimes has focused on the developed countries. Since the recent crises in emerging markets, however, attention has shifted to the choice of exchange rate regimes for developing countries, especially those that are more integrated into the world capital markets. In Too Sensational, W. Max Corden presents a systematic and accessible overview of the choice of exchange rate regimes. Reviewing many types of regimes, he shows how the choice of an exchange rate regime is related to both fiscal policy and trade policy. Building on the theory of optimum currency areas, Corden develops an analytic framework of three approaches (nominal anchor, real targets, and exchange rate stability) and three polar exchange rate regimes (absolutely fixed, pure floating, and fixed but adjustable). He considers all other regimes to be mixtures of two or three of the polar regimes. Beginning with theory and later turning to case studies of countries in Asia, Europe, and Latin America, Corden focuses on how economies react to negative and positive shocks under various exchange rate regimes. He examines in particular the Asian and Latin American currency crises of the 1990s. He concludes that although "too sensational" crises have discredited fixed but adjustable regimes, the extremes of absolutely fixed regimes or pure floating regimes need not be chosen.